Early Psychomotor Advantage in Moderately Preterm Twins Born between 32 and 33 Weeks - Turriziani, Laura; Cafeo, Anna; Pino, Gaetana; Vetrano, Noemi; Alibrandi, Angela; Di Rosa, Gabriella (Journal of Pediatric Neurology, 2020)
Twin birth may represent a challenging event often associated with prematurity. We previously reported on developmental trajectories in preterm children categorized by gestational age. Based on the same study population, in this study we investigated the influence of gemellarity on the neurodevelopment of 73 twins (26.4%) and 207 singletons (73.6%), categorized into three groups according to their gestational age. The age of the achievement of developmental milestones between the three groups and the influence of preperinatal events on neurodevelopment were analyzed. An early neurodevelopmental advantage was detected in preterm twins born between 32 and 33 weeks. Environmental and nurturing factors may explain these findings.
Keywords: twins; milestones; preterm; development; psychomotor